Information Technology Service Management Framework Selection through Analytic Hierarchy Process in an Energy Company - Rachmadianto, Faisal; Adhiutama, Akbar (The Indonesian Journal of Business Administration, 2015)
Abstrac.tDependency of companies on Information Technology (IT) is increasing significantly for the last decade. IT infrastracture has risen so complex teamed with company requirement to cut costs and always adhere with regulation. It has pushed companies in searching processes in order to increase their efficiency in managing IT operations. The current IT organization model and services in one of the biggest oil and gas Company in Indonesia have been questioned by many customers regarding with its performance, service satisfaction and customer oriented process. The management through voice of customer demanded to have improvement in current IT service management processes. Information technology service management (ITSM) is a study to manage organizations or companies providing services of IT based on a customerâ€™s point of view. It is required to change or shift to a service-oriented approach from technology-oriented in managing IT. It will make business process between IT and business change so that they will work together starting from defining until delivering IT services.To select the best ITSM frameworks that suit with the Company, Analytic Hierarchy Process (AHP) methodology is being applied. AHP as one of the multi criteria decision making approach with benefit, opportunity, cost, and risk (BOCR) analysis as the technique to determine the best alternatives of IT service management framework considering several factors of criteria and sub-criteria. It involves several employees across IT functions and customer representatives to develop these criteria. Based on AHP with BOCR analysis, this study concludes the solution of implementing Information Technology Infrastructure Library (ITIL) with End-to-End Model and Lean Sigma is the best alternative (0.4279). The solution is the best to improve customer satisfaction, closer business and IT alignment and quick IT response to manage business needs. The second priority of the solution is implement ITIL (0.2567) followed by Implement MOF (0.1678) and last priority is Implement CoBit (0.1475). The implication with this solution is to have reorganization that will need support from management of the company. To lead the big change, John Kotter's 8-step change model is being applied on the implementation plan.Keywords: Analytic Hierarchy Process, information technology service management, information technology infrastructure libraryÂ